2005
DOI: 10.1194/jlr.m500042-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Higher order lipase gene association with plasma triglycerides

Abstract: Lipoprotein lipase, HL, and endothelial lipase (EL) are proteoglycan-bound enzymes that regulate plasma lipoprotein levels through coordinated triglyceride (TG) lipase and phospholipase activity. We hypothesized that single nucleotide polymorphisms (SNPs) in lipase genes would have higher order impact on plasma lipoproteins beyond the influence of individual SNPs. In a sample of asymptomatic Caucasian subjects (n ‫؍‬ 738), we used a two-stage approach, first identifying groups of subjects with similar multiloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Considering the redundant enzymatic activities and substrate specifi cities and the distinct, yet overlapping expression patterns of lipases, such interactions may have important contributions to dyslipidemia and atherosclerotic cardiovascular disease. For example, an association analysis of LPL, HL, and EL variants revealed genetic interaction in the determination of plasma TG levels in a normal population ( 47 ). To investigate the interaction between HL and EL directly, Brown et al ( 17 ) recently generated HL/EL double-knock-out mice representing the fi rst engineered mouse model of combined lipase defi ciency.…”
Section: Lmf1 Defi Ciency Diminishes Post-heparin Phospholipase Activitymentioning
confidence: 99%
“…Considering the redundant enzymatic activities and substrate specifi cities and the distinct, yet overlapping expression patterns of lipases, such interactions may have important contributions to dyslipidemia and atherosclerotic cardiovascular disease. For example, an association analysis of LPL, HL, and EL variants revealed genetic interaction in the determination of plasma TG levels in a normal population ( 47 ). To investigate the interaction between HL and EL directly, Brown et al ( 17 ) recently generated HL/EL double-knock-out mice representing the fi rst engineered mouse model of combined lipase defi ciency.…”
Section: Lmf1 Defi Ciency Diminishes Post-heparin Phospholipase Activitymentioning
confidence: 99%
“…For example, the combined effect of LPL, LIPE and LIPC accounted for 4.4% variation in HDL-C levels and had a better ability to predict the HDL-C levels than any single lipase gene. Similarly, the cumulative genetic effect of the lipase genes was previously reported [28]. Since we did not find any interactions between the lipase genes, the overall impact of multiple lipase genes is likely due to an additive rather than multiplicative effect.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study has observed that the apo CIII-SstI SNP increases fasting TG levels among carriers of the LPL P207L mutation. 30 Reilly et al 31 have also recently…”
Section: Discussionmentioning
confidence: 99%